Literasi Mengenai Penerapan Komunikasi Inter Personal Antara Orang Tua dengan Anak untuk Meningkatkan Perilaku Positif Anak - Setyo Purwanto; Diana Sukorina; Aurora Luna Marsela; Doni Mardiyanto; Abdullah Zailani (Fakultas Ekonomi Universitas Surakarta, 2024)
Abstract From the past until now, many parents feel confused and difficult in shaping positive behavior in children. Parents also often feel unable to understand their children's behavior that always tests their patience, so it is not uncommon for parents to become angry and apply punishment to children. This has an impact on the formation of children's perceptions that become negative towards parents. The child will feel that he is not understood, causing him to behave negatively such as lying, not doing his responsibilities at home, and others. One of the efforts that can be made to improve children's positive behavior is for parents to apply effective communication to children in interaction. With this Community Service Activity, it is hoped that it can provide new understanding, knowledge and skills for parents in implementing interpersonal communication with children. Therefore, a warm relationship between parents and children can be established, so that it is followed by positive behavior in children that will also increase. Activities are carried out using the counseling method, namely interpersonal by providing understanding and knowledge related to interpersonal communication so that it becomes a new skill that parents will learn in applying communication when interacting with children. The results of this activity show that parents gain new understanding, knowledge and skills related to applying interpersonal communication when interacting with children. In addition, parents realize that the communication applied so far with children is not appropriate, causing frequent conflicts and having an impact on children's negative behavior. Keywords : Personality Communication, Parents, Children's Positive Behavior